1987
DOI: 10.1128/jcm.25.11.2159-2162.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic relationship between the animal and human pathogen Pythium insidiosum and nonpathogenic Pythium species

Abstract: Identification of the newly named pathogenic oomycete Pythium insidiosum and its differentiation from other Pythium species by morphologic criteria alone can be difficult and time-consuming. Antigenic analysis by fluorescent-antibody and inmunodiffusion precipitin techniques demonstrated that the P. insidiosum isolates that cause pythiosis in dogs, horses, and humans are identical and that they were distinguishable from other Pythium species by these means. The immunologic data agreed with the morphologic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 7 publications
2
25
0
1
Order By: Relevance
“…A case of eorneal uleer due to Pythium was reported in the same series. Two cases of subcutaneous pythiosis, also in thalassemics, have been cited in the literature (6,7,8,9) but no clinical or histopathologic data have been presented. Hemoglobin eleetrophoresis was not performed in the present 2 cases but mean corpuscular volume and red cell morphology were normal in both cases, virtually excluding thalassemia trait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A case of eorneal uleer due to Pythium was reported in the same series. Two cases of subcutaneous pythiosis, also in thalassemics, have been cited in the literature (6,7,8,9) but no clinical or histopathologic data have been presented. Hemoglobin eleetrophoresis was not performed in the present 2 cases but mean corpuscular volume and red cell morphology were normal in both cases, virtually excluding thalassemia trait.…”
Section: Discussionmentioning
confidence: 99%
“…Pythium is the usual causative organism in canine gastrointestinal phycomycosis (2) and it is a well known pathogen in plants (3) and fish (4). Despite its widespread occurrence in tropical and subtropical areas including the USA, Australia, New Cuinea, Indonesia and Brazil (5), Pyt/iium has not been recognized as a human pathogen until recently, jythimn has now been implicated in human disease (6,7) including 6 cases of medium and large vessel arteritis (7,8) and 2 cases of subcutaneous infection (9). The isolates from the latter cases were shown to be morphologically and antigenically identical to Pythium isolates causing disease in dogs and horses (6,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…destruens with 1? insidiosum was suggested recently (16), the present study was carried out to elucidate the antigenic relationship between the holotypes of l? insidiosum de Cock et al 1987 (6) and I?…”
Section: Miller O'neil Et Al and Shiptonmentioning
confidence: 95%
“…(19,23,25) speculated as to whether the etiologic agent of pythiosis represented a single or a number of species of Pythium. In a recent collaborative antigenic study, Mendoza et al (16) found that the isolates from animals and humans around the world shared antigens and these strains are a single species that could be identified as E? insidiosum by immunodiffusion (ID) and fluorescent antibody tests.…”
Section: Introductionmentioning
confidence: 99%